First‐Generation Student Veterans: Implications of Poverty for Psychotherapy. Issue 2 (20th December 2012) - Wurster, Kristin G.; Rinaldi, Anthony P.; Woods, Tamara S.; Liu, William Ming
<x xml:space="preserve">Abstract</x> Student veterans are arriving at university and college campuses and many counselors may not be prepared. Multiple and intersecting identities complicate the student's integration and matriculation into higher education. We review literature on first‐generation college students and issues pertinent to student veterans. Using the revised Social Class Worldview Model, this article offers a case example to illustrate how counselors may best work with student veterans.